Experimental Evaluation of Conditions for Short-distance Transmission of Event Timing Data - Bilinskis, I.; Skageris, A.; Sudars, K. (Elektronika ir Elektrotechnika, 2013)
Specifics of event timing data transmission are experimentally investigated under conditions typical for multi-channel data acquisition from a large quantity of signal sources. The events, in the considered case, are analog input signal and sinusoidal reference function crossings. The sequences of the crossing time instants represent the respective analog input signals and these sequences have to be transmitted to the signal reconstruction subsystem. An experimental system for fast short-distance transmission has been built. It performs data encoding on the basis of digital pulse position modulation with 10 picoseconds resolution. The achievable data encoding resolution and other vital parameters characterizing data transmission systems of this type were evaluated on this basis. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.4055